A Case of Pancreatic Neuroendocrine Tumor with Liver Metastases Demonstrating the Possibility of Enhanced ACTH Production by the SACI Test - Hirozumi Mori; Masashi Tamura; Ryo Ogawa; Yuta Kimata; Sho Endo; Katsutoshi Sekine; Sayuri Kodama; Hiromi Hisazumi Watanabe; Kiyoshi Ookuma; Masahiro Jinzaki (Case Reports in Endocrinology)
Objective. ACTH-producing pancreatic NETs have a propensity to metastasize, and in patients with metastases, there is no established method yet to precisely determine if the excess ACTH is produced by the primary or the metastatic tumors. Localizing the source of production of ACTH in such cases is important for devising suitable treatment strategies and evaluating the benefit of local therapies from the viewpoint of control of Cushing’s syndrome. Methods. We performed the selective arterial calcium injection (SACI) test combined with selective portal and hepatic venous sampling in a 32-year-old female patient with ectopic ACTH-producing pancreatic NET and liver metastases. Results. The blood level of ACTH after Ca loading was significantly elevated only in the vessels thought to be directly feeding the pancreatic tumor, and Ca loading from any artery did not significantly increase ACTH concentrations in the hepatic veins compared to the main trunk of the portal vein. Conclusions. The present case demonstrates that there might be an ACTH-producing p-NET that responds to Ca loading. Further in vitro studies are required to validate this possibility.